Hidden Hunger or Knowledge Hunger? an Interventional Study in a Public School of Rawalpindi - Mashhadi, Syed Fawad; Khan, Nazish; Maryam, Zunera; Aamir, Manal; Sahi, Saman Sajjad; Amin, Maira (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To assess baseline micronutrient knowledge among adolescents in a school of Rawalpindi and to determine effect of educational intervention on micronutrient knowledge and food choices. Study Design: Quantitative pre and post-intervention study Replace and During of Study: A Public school of Rawalpindi Pakistan from Nov 2021-Apr 2022 Methodology: A sample size of 190 was obtained by using Raosoft sample size calculator. Considering 15% non-response final sample size of 230 was taken. Study participants included students of 9th–12th grades enrolled through non probability convenience sampling. A pre-test was taken to assess baseline micronutrient knowledge using standardized, pretested questionnaires. Five invalid responses were excluded, yielding a total of 225. Intervention was carried out via an interactive multimedia lecture on micronutrients. After eight weeks, 217 out of those students were reassessed via same questionnaire. Data was analysed using SPSS Version-25. Qualitative variables were expressed as frequency and percentages and quantitative variables as mean and S.D. Paired sample t-test (for continuous variables) and Chi-square test (for categorical variables) were applied. Results: Out of 217 participants, 66(30%) were males and 151(70%) were females with a mean age 16.8±0.7 years. Significant improvement was seen on general micronutrient knowledge and knowledge of iron, vitamin A, vitamin D, zinc, calcium and folate (p-value < 0.05). There was a moderate improvement in food consumption in a frequency of 2-3 times/week. Conclusion: The intervention improved micronutrient knowledge and positively impacted food choices. Thus, such knowledge-based programs are recommended.